2004
DOI: 10.1208/pt050454
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic excipients modulate the time lag of time-controlled disintegrating press-coated tablets

Abstract: An oral press-coated tablet was developed by means of direct compression to achieve the time-controlled disintegrating or rupturing function with a distinct predetermined lag time. This press-coated tablet containing sodium diclofenac in the inner core was formulated with an outer shell by different weight ratios of hydrophobic polymer of micronized ethylcellulose (EC) powder and hydrophilic excipients such as spray-dried lactose (SDL) or hydroxypropyl methylcellulose (HPMC). The effect of the formulation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Indeed, larger particle dimensions were associated with a higher porosity thus resulting in enhanced shell permeability. As expected, the incorporation of swellable (HPMC, sodium starch glycolate, sodium alginate, glycine max husk) and osmotic (sodium chloride) excipients into the core formulation or of hydrophilic compounds (HPMC, spray-dried lactose) into the outer shell was reflected in shorter delay phases (Lin et al, , 2004aRane et al, 2009). Modifications of half of the coating formula were demonstrated to be a further means of modulating the lag phase.…”
Section: Delivery Systems Based On Release-controlling Coatingssupporting
confidence: 61%
“…Indeed, larger particle dimensions were associated with a higher porosity thus resulting in enhanced shell permeability. As expected, the incorporation of swellable (HPMC, sodium starch glycolate, sodium alginate, glycine max husk) and osmotic (sodium chloride) excipients into the core formulation or of hydrophilic compounds (HPMC, spray-dried lactose) into the outer shell was reflected in shorter delay phases (Lin et al, , 2004aRane et al, 2009). Modifications of half of the coating formula were demonstrated to be a further means of modulating the lag phase.…”
Section: Delivery Systems Based On Release-controlling Coatingssupporting
confidence: 61%
“…It is preferred by the formulators to modulate drug release mainly due to its claim to form strong viscous gel in contact with water. 16 Formulation IX-HPMC was designed to evaluate the effect of HPMC on drug release from central core matrix tablet. Figure 3 shows the release profile of indomethacin from HPMC loaded press coated tablets.…”
Section: Resultsmentioning
confidence: 99%
“…[5] A literature survey on this subject revealed that the type of excipient and the amount used influenced the controlled drug release profile from tablets and this affected the drug bioavailability. [6] Besides biocompatibility, solubility is one of the important factors that has to be considered when designing a controlled release system. Considering the advantages derived from their molecular structure, water-soluble cellulose ethers are currently the most commonly used matrix polymers.…”
Section: Introductionmentioning
confidence: 99%